The Impact of the 13-Valent Pneumococcal Conjugate Vaccine on Pneumococcal Carriage in the Community Acquired Pneumonia Immunization Trial in Adults (CAPiTA) Study. (6th January 2018) - van Deursen, Anna M M; van Houten, Marlies A; Webber, Chris; Patton, Michael; Scott, Daniel; Patterson, Scott; Jiang, Qin; Gruber, William C; Schmoele-Thoma, Beate; Grobbee, Diederick E; Bonten, Marc J M; Sanders, Elisabeth A M
Abstract: Background: The impact of pneumococcal conjugate vaccination on the prevalence of nasopharyngeal carriage with pneumococci and other bacteria in adults is unknown. The direct effects of the 13-valent pneumococcal conjugate vaccine (PCV13) in community dwelling older adults was investigated as part of the randomized controlled Community Acquired Pneumonia immunization Trial in Adults (CAPiTA). Methods: We determined the carriage of Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae, and Moraxella catarrhalis before and 6, 12, and 24 months after vaccination using polymerase chain reaction (PCR)–based methods and conventional cultures of nasopharyngeal and oropharyngeal swab samples in 1006 PCV13 recipients and 1005 controls. Serotyping of the 13 vaccine-type (VT) pneumococci was performed by PCR targeting capsular synthesis genes and Quellung reaction of isolates. Results: Before randomization and based on PCR, 339 of 1891 subjects had nasopharyngeal carriage with any pneumococci (17.9%), and 114 of 1891 (6.0%) carried VT pneumococci. At 6 months after vaccination, VT pneumococcal carriage was significantly lower in PCV13 recipients than in the placebo group (relative risk, 0.53; 95% confidence interval, .35–.80; P = .04). There was no difference between the groups at 12 and 24 months after vaccination. Carriage of non-VT pneumococci, S. aureus, H. influenzae, and M. catarrhalis did not change between groups. Conclusions: In community-dwelling adults aged ≥65 years, a single dose of PCV13 seems to elicit a small and temporary reduction in VT carriage 6 months after vaccination. Neither replacement by non-VT serotypes nor impact on other nasopharyngeal bacteria was observed. Abstract : In community-dwelling adults aged ≥65 years, 13-valent pneumococcal conjugate vaccine seems to elicit a small, temporary reduction in nasopharyngeal carriage of vaccine-type pneumococci 6 months after vaccination. Neither replacement by nonvaccine serotypes nor impact on other nasopharyngeal bacteria was observed.